Antibody Response and Maternofetal Antibody Transfer in SARS-CoV-2-Positive Pregnant Women: A Multicenter Observational Study - Enengl, Sabine; Pecks, Ulrich; Oppelt, Peter; Stelzl, Patrick; Trautner, Philip Sebastian; Shebl, Omar; Lamprecht, Bernd; Longardt, Ann Carolin; Eckmann-Scholz, Christel; Keil, Corinna; Mand, Nadine; von Kaisenberg, Constantin Sylvius; Jegen, Magdalena; Doppler, Stefan; Lastinger, Julia (Geburtshilfe und Frauenheilkunde, 2022)
Introduction Awareness of SARS-CoV-2 infection in pregnant women and the potential risk for infection of their neonates is increasing. The aim of this study was to examine the immune status of affected women and evaluate the dynamics of placental antibody transfer.Materials and Methods The study included 176 women with SARS-CoV-2 infection during pregnancy who delivered between April 2020 and December 2021 at eight obstetric maternity sites. Demographic data, maternal and neonatal characteristics were summarized. Antibody testing for IgA and IgG in maternal blood sera and umbilical cord samples was evaluated and IgG transfer ratios were calculated. Values were related to the time of infection during pregnancy and birth.Results The percentage of IgG positive women increased from 29.0% (95% CI 23.8 – 37.8) at presentation with a positive PCR test result to 75.7% (95% CI 71.6 – 79.8), the percentage of IgG positive umbilical cord blood samples increased from 17.1% (95% CI 13.0 – 21.3) to 76.4% (95% CI 72.2 – 80.7) at more than six weeks after infection. Regression lines differed significantly between maternal and fetal IgG responses (p < 0.0001). Newborns react with a latency of about one week; umbilical cord blood antibody concentrations are highly correlated with maternal concentration levels (ρ = 0.8042; p < 0.0001). IgG transplacental transfer ratios were dependent on infection-to-birth interval. Two of the umbilical cord blood samples tested positive for IgA.Conclusions These findings confirm vertical SARS-CoV-2 transmission is rare; however, antibodies are transferred to the fetus soon after infection during pregnancy. Since transplacental antibody transfer might have a protective value for neonatal immunization this information may be helpful when counseling affected women.
Keywords: antibody; COVID-19; pregnancy; SARS-CoV-2